The violence dynamics in public security: Military interventions and police-related deaths in Brazil - Suarez, Marcial A.G.; De Souza, Luís Antônio Francisco [UNESP]; Serra, Carlos Henrique Aguiar (Onati International Institute for the Sociology of Law, 2021)
This paper discusses the deadly use of violence as a public security agenda, focusing on police lethality and military interventions. Through a literature review to understanding concepts – such as “war,” for example – used in public security policy agendas, the study seeks to frame the notion of political violence, mainly referring to the policies designed to combat violence in Brazil. The objective is to problematize the public security policy based on the idea of confrontation, which adopts the logic of war and the notion of “enemy”. The paper is divided into three parts. The first is a conceptual approach to violence and war, and the second is the analysis of the dynamic of deadly use of force. Finally, the third part is a contextual analysis of violence in Rio de Janeiro, its characteristics, and central actors, using official statistics on violence in the region.
Keywords: Brazil; Military interventions; Police lethality; Public security